Role of the gut microbiota in hematologic cancer - Guevara-Ramírez, Patricia; Cadena-Ullauri, Santiago; Paz-Cruz, Elius; Tamayo-Trujillo, Rafael; Ruiz-Pozo, Viviana A.; Zambrano, Ana Karina (Frontiers in Microbiology, 2023)
Hematologic neoplasms represent 6.5% of all cancers worldwide. They are characterized by the uncontrolled growth of hematopoietic and lymphoid cells and a decreased immune system efficacy. Pathological conditions in hematologic cancer could disrupt the balance of the gut microbiota, potentially promoting the proliferation of opportunistic pathogens. In this review, we highlight studies that analyzed and described the role of gut microbiota in different types of hematologic diseases. For instance, myeloma is often associated with Pseudomonas aeruginosa and Clostridium leptum, while in leukemias, Streptococcus is the most common genus, and Lachnospiraceae and Ruminococcaceae are less prevalent. Lymphoma exhibits a moderate reduction in microbiota diversity. Moreover, certain factors such as delivery mode, diet, and other environmental factors can alter the diversity of the microbiota, leading to dysbiosis. This dysbiosis may inhibit the immune response and increase susceptibility to cancer. A comprehensive analysis of microbiota-cancer interactions may be useful for disease management and provide valuable information on host-microbiota dynamics, as well as the possible use of microbiota as a distinguishable marker for cancer progression.